Consequences of Domestication on Gut Microbiome: A Comparative Study Between Wild Gaur and Domestic Mithun - Prabhu, Vandana R.; Wasimuddin,; Kamalakkannan, Ranganathan; Arjun, Moolamkudy Suresh; Nagarajan, Muniyandi (Frontiers in Microbiology, 2020)
Although gut microbiome benefits the host in several ways, how anthropogenic forces impact the gut microbiome of mammals is not yet completely known. Recent studies have noted reduced gut microbiome diversity in captive mammals due to changes in diet and living environment. But, no studies have been carried out to understand how gut microbiome of wild mammals responds to domestication. We analysed the gut microbiome of wild and captive gaur and domestic mithun (domestic form of gaur) to understand whether the gut microbiome exhibits sequential changes from wild to captivity and after domestication. Both captive and domestic populations were characterized by reduced microbial diversity and abundance as compared to their wild counterparts. Notably, two beneficial bacterial families Ruminococcaceae and Lachnospiraceae, which are known to play vital roles in herbivores’ digestion, exhibited lower abundance in captive and domestic populations. Consequently, the predicted bacterial functional pathways especially related to metabolism and immune system showed lower abundance in captive and domestic populations compared to wild population. Therefore, we suggest that domestication can impact the gut microbiome more severely than captivity which might lead to adverse effects on host health and fitness. However further investigations are required across a wide range of domesticates in order to understand the general trend of microbiome shifts in domestic animal.